HRM in VHE: Leadership, Employee Engagement and Work Environment - Nazarwin, Nazarwin; Wardi, Yunia; Rino, Rino (Relevance: Journal of Management and Business, 2024)
Human Resource Management (HRM) is the key to the failure or success of educational institutions. The three main factors that influence HRM at Poltekpel Sumbar are leadership, employee engagement and work environment. The purpose of this study is to see the relationship between these four factors including leadership, work environment, employee engagement and HRM at Poltekpel Sumbar. This study was conducted at Merchant Marine Polytechnic of West Sumatera. The research participants were all employees with a total of 154 people. The research instrument was a questionnaire. Data collection was carried out by giving questionnaires directly to the participants. The questionnaire data analysis technique was carried out using linear regression. The conclusion of this study indicated that there is a significant influence of leadership on HRM, employee engagement on HRM, employee engagement on the work environment, and leadership on the work environment. Meanwhile, there is no significant influence of the work environment on HRM and leadership on employee engagement. Further research can also examine in more depth other research variables related to HRM in all vocational higher education institution under the Ministry of Transportation, namely in the maritime, land and railway and aviation institution.